Media Dan Sumber Belajar Dalam Pembelajaran PAI - Syahvira Indah Puspita; Sari, Meilia Kumala (Journal of International Multidisciplinary Research, 2024)
To achieve the goals of Islamic education, in the learning process teachers should use learning media. By using learning media, teachers will more easily teach subject matter and students will more easily understand the lesson. The characteristics of Islamic learning media can be grouped into graphic media, audio media and silent projection media. Based on how it is obtained, media is divided into finished media and designed media. When choosing media, you need to pay attention to the media selection criteria. By using media in the learning process, it is hoped that the quality of Islamic religious education will be even better. This article also discusses learning resources in learning Islamic Religious Education. The importance of learning resources in learning cannot be denied, learning resources are anything, whether objects, data, places, facts, ideas or people that can trigger the learning process. Learning resources can be classified into several types such as people, materials, environment, activities, tools and equipment. From here learning resources are classified into printed, non-printed learning resources, facilities, activities and environment. Of course, with the current development of information technology, it can help students to get various learning resources from all directions, so that students will be more active and creative in learning.